Konseling Analisis Transaksional dengan Menggunakan Teknik Empty Chair untuk Meningkatkan Perilaku Asertif Peserta Didik Korban Bullying - Mayang, Sri; Kasih, Fitria; Nita, Rahma Wira (INSIGHT: Jurnal Bimbingan Konseling, 2025)
The aim of this research is to determine the effectiveness of transactional analysis counseling using the empty chair technique to measure the level of assertiveness of students who are victims of bullying. However, some students who are victims of bullying at SMAN 1 Gunung Talang have low assertive behavior. This quantitative research with an experimental approach uses a one group pretest-posttest design. The sample is students who are victims of bullying with a low level of assertiveness. Measurements were carried out using questionnaire instruments and by conducting individual counseling with two treatment sessions or treatment with individual counseling using the empty chair technique. The research results showed a significant increase in the assertive behavior of students who were victims of bullying, with the average score increasing from 118 in the pretest to 178 in the posttest and a t-count of 0.0285 with a degree of freedom of 2. The t-test value was used to determine each independent variable against the dependent variable. If the t count ˃ t table or the significance value of the t test is 0.05 then it can be concluded that individually the independent variable has a significant effect on the dependent variable, then the explanation obtained is the sig value. (2-failed) = 0.0285 ˂ 0.05 means that this test is significant or that there is a difference in the average assertive behavior before and after carrying out transactional analysis counseling using the empty chair technique. This means that there is a significant difference from transactional analysis counseling using the empty chair technique to increase the assertive behavior of students who are victims of bullying